Recommended vaccinations for patients with chronic liver diseases - Janocha-Litwin, Justyna; Simon, Krzysztof (Clinical and Experimental Hepatology, 2025)
Patients with chronic liver diseases, particularly those with liver cirrhosis, are more vulnerable to severe superinfections compared to the general population. They face an increased risk of liver function decompensation and mortality when contracting viral or bacterial infections. Vaccination is crucial in mitigating these risks, yet its efficacy in this patient group may be limited. Despite the safety of vaccines, their effectiveness in individuals with chronic liver diseases remains constrained. A significant challenge is the inadequate implementation of vaccination protocols, often due to insufficient communication and recommendations from physicians, including hepatologists, and the high cost of vaccines.